ENTRE LO MODERNO Y LO TRADICIONAL: RELATO DE UNA EXPERIENCIA DE APRENDIZAJE EN PROGRAMACIÓN DE COMPUTADORES - Omar Iván Trejos Buriticá; Luis Eduardo Muñoz Guerrero; Jorge Iván Ríos Patiño (Revista Ingeniería, Matemáticas y Ciencias de la Información)
The confrontation between the modern and the traditional is an important side in education research. This articlepresents the results of an investigation carried out in the classroom, where the effectiveness of learning is compared fromthe use of the cell phone camera compared to the traditional way of copying in the notebook, within a mutually exclusivemethodology to make observations with objectivity. The results show that although technological advances facilitatesome activities of the human being in a learning context that does not necessarily means it enables the learning ofdisciplinary knowledge. On the other hand, the traditional ways of consigning the knowledge imparted by the teacher inhis keynote presentation, that is, copying by hand and letter, allow the student a direct contact with the knowledgementioned and its impact on learning is more effective. It is concluded that in a context of technological learning, theengineer teacher must be clear when to use certain modern technological resources and when to open the spaces for thestudent to register, from his own perspective, the new knowledge acquired.